2012
DOI: 10.1002/pola.25899
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ladder‐like polynorbornenes with n‐type perylenendiimide derivatives as bridges

Abstract: Polymerizable tetrachloro‐perylenediimdes containing endo/exo‐norbornene groups on both imide sides were designed and synthesized. Endo/Exo‐type soluble ladder‐like polynorbornenes with perylenediimide (PDI) as bridges were prepared by ring‐opening metathesis polymerization (ROMP). XRD characterizations showed that the ladder‐like polynorbornenes had ordered structures similar to the supramolecular precursors assembled from the corresponding monomers. TGA measurements demonstrated great thermal stabilities for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The reason for the low molecular weight characteristics of both polymers are not completely understood, however, we attributed this to the insufficient solubility of the polymers in the eluent or significant chain transfer that is happening during the fast ROMP while using the G3 initiator. Never the less the low molecular weight characteristics of both poly M1 and poly M2 are comparable to the ROMP‐derived poly(norbornene)s reported by others 31,33 …”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…The reason for the low molecular weight characteristics of both polymers are not completely understood, however, we attributed this to the insufficient solubility of the polymers in the eluent or significant chain transfer that is happening during the fast ROMP while using the G3 initiator. Never the less the low molecular weight characteristics of both poly M1 and poly M2 are comparable to the ROMP‐derived poly(norbornene)s reported by others 31,33 …”
Section: Resultssupporting
confidence: 73%
“…This methodology can generate a wide variety of high molecular weight polymers in a controlled regioregular and stereoregular manner 28,29 . To date, only a few examples have been reported for the synthesis of ROMP‐derived PDI‐grafted poly(cycloolefin)s and most of the building blocks have been functionalized at the imide ‐linkage on the PDI pendant 25,30–36 . In 2012, Li et al reported an example of such imide ‐functionalized PDI‐based ladder‐type poly(norbornene)s and studied their supramolecular behavior 31 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…But their poor solubilities make them difficult to process even in solution, not to mention on solid substrates. We have reported two ordered ladder‐like polymers based on PBI derivatives to improve the materials’ thermal stability and solubility while retaining their optoelectronic properties in solution and in the bulk state 16d. 17 Herein, we report a facile method to prepare surface‐tethered polymeric semiconductor films using two novel ε‐ N ‐PBI functionalized L ‐lysine N ‐carboxylic anhydride (NCA) derivatives via SI‐ROP on silicon wafers for potential use in molecule electronic devices.…”
Section: Methodsmentioning
confidence: 99%